2011
DOI: 10.1007/s10165-011-0524-6
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib, a cyclooxygenase-2 inhibitor, improved upper gastrointestinal lesions in rheumatoid arthritis patients as assessed by endoscopic evaluation

Abstract: We prospectively evaluated the effects of celecoxib (CEL) on the gastrointestinal (GI) tract of rheumatoid arthritis (RA) patients with endoscopically identified GI mucosal injury after therapeutic switching from the long-term use of traditional nonsteroidal anti-inflammatory drugs (NSAIDs). Upper GI endoscopy was performed on RA patients who had been treated with NSAIDs for ≥3 months. GI mucosal injury was evaluated according to the modified LANZA score. Patients with mucosal injury without ulcers were switch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…This study argues that the celecoxib-induced stomach, liver and brain lesions resulting from extended COX-2 inhibition are a function of NO system dysfunction, which is particularly worsened after a high-dose application. Considering the advanced safety profile of celecoxib[ 10 ], lower celecoxib regimens such as 200 mg/kg and 500 mg/kg given intraperitoneally were without notable effect on gastric, liver or brain lesions (thus, these results are not specifically shown). These lesions could be all influenced by the NOS substrate L-arginine and in particular by the stable pentadecapeptide BPC 157, which is an agent known to counteract non-selective NSAID-induced ulcerogenesis as well as the liver and brain lesions that interact with the NO system[ 1 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study argues that the celecoxib-induced stomach, liver and brain lesions resulting from extended COX-2 inhibition are a function of NO system dysfunction, which is particularly worsened after a high-dose application. Considering the advanced safety profile of celecoxib[ 10 ], lower celecoxib regimens such as 200 mg/kg and 500 mg/kg given intraperitoneally were without notable effect on gastric, liver or brain lesions (thus, these results are not specifically shown). These lesions could be all influenced by the NOS substrate L-arginine and in particular by the stable pentadecapeptide BPC 157, which is an agent known to counteract non-selective NSAID-induced ulcerogenesis as well as the liver and brain lesions that interact with the NO system[ 1 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was previously shown that celecoxib improved gastric lesions[ 10 ], induced the regression of preneoplastic lesions in the liver[ 11 ] and counteracted brain lesions and convulsions[ 12 - 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…And, treatment with COX-2-selective NSAIDs might help resolve this issue in RA patients. It has already been reported that COX-2-selective NSAIDs have a gastric ulcer-protective effect compared with non-selective NSAIDs in RA patients [ 26 , 27 ]. Our present study also demonstrated that the modified LANZA score of RA patients treated with COX-2-selective NSAIDs was lower than that in RA patients treated with non-selective NSAIDs.…”
Section: Discussionmentioning
confidence: 99%
“…The protocol encouraged use of misoprostol (100 µg once daily) for gastropathy prophylaxis, buffered aspirin (81 mg once daily) for cardiovascular prophylaxis, and celecoxib (200 mg twice daily) for rheumatoid arthritis based on the limited amount of evidence of safety and efficacy. 14-17 Enrolled residents received standard care, guaiac test at baseline and conclusion as well as symptom questionnaire at baseline, every 3 weeks, and at conclusion. Nurses, residents, pharmacists, and physicians were educated about the harms, intents, methods, and duration of the protocol.…”
Section: Methodsmentioning
confidence: 99%